Memorable tourism experiences nostaliga and revisit intention on transformed tourist attractions - Gaudensius Djuang; Engelbertus G. C. Watu; Selfiana Goetha (Enrichment : Journal of Management, 2023)
This study aims to examine the effect of Memorable Tourism Experience on the intention to revisit with nostalgia as a mediating variable in renovated tourist destinations where, the destination still offers the same thing but with a different appearance. The author examines tourism destinations in Kupang City that are being improved in order to increase their core competitiveness and generate tourist visit intentions. The methodological approach consists of three types: interview, observation and survey. The sampling technique used is convenience sampling. Of the 203 questionnaires we distributed, 172 respondents answered that they had visited Tedis Beach and were willing to continue answering 14 questions related to research. The results showed the influence of Memorable Travel Experiences on the intention to revisit tourist attractions that have been transformed. But nostalgia does not directly affect the intention to visit again. This research can be an information, consideration, and contribution of ideas for stakeholders in an effort to increase interest in visiting Tedis Beach Kupang. It is hoped that future research can develop other elements that can increase MTE such as: psychological factors, culture, environmental factors, and interrelational factors. In addition, it can offer both positive and negative experiences that involve international tourists as research objects